Secondary school students’ perceptions about science: An art-based research - MERTOĞLU, HATİCE (My University, 2023)
This paper discusses how secondary school students perceive science, scientist and science environment. Students’ perceptions about science have been studied by various researchers with different participants. Based on the knowledge gained from previous research studies, this research focuses on h ow recent developments in the world, for example pandemic and Maraş earthquake, affected secondary students' perceptions about science. Art based research is used in this research. Research participants were 30 sixth grade students attending a secondary school in Devrek, Zonguldak, Türkiye. Students were chosen randomly from sixth grade class taught by one of the researchers. The research questions of this study are 1.What is science?, 2.Who is the scientist?, 3. How is the science environment?. For the first question, students were asked to write a definition about science. For the others, participants were asked to draw a Picture of scientist in a science environment. Data was collected through essays and pictures were analyzed with a software designed for qualitative and mixed methods research. Findings were discussed within the framework of the literature.
Keywords: nature of science; art-based research; students’ perceptions; qualitative research